Coastal Area Management and Environmental Law Enforcement Against Marine Debris Polling - Kartika, Eka Dewi; Laitupa, Salma; Sulaeman, Sulaeman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
In the implementation of coastal and marine resource management, it is essentially aimed at empowering the socio-economic community, so the community should have great power to regulate itself in managing coastal and marine resources in this era of autonomy. The process of transferring authority from the government to the community must be realized. Law enforcement against coastal areas is very complex, as intended by Law Number 32 of 2009, namely through several instruments, namely administration, civil and criminal, but first the community must understand the legal awareness itself. In an effort to foster legal awareness, repressive, preventive and persuasive actions can be taken.